Pengaruh Ulasan Pengunjung Online terhadap Adopsi Informasi oleh Wisatawan Muda - Aqlia Pratiwi; Bambang Dwi Prasetyo; Ananda Sabil Hussein (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2025)
The rapid growth of digital platforms in Indonesia has changed the way young travelers adopt information. Young travelers increasingly rely on user-generated content available on digital platforms, particularly Online Consumer Reviews (OCR) such as Google Reviews. This study examines the impact of the central route dimensions, which are part of the Elaboration Likelihood Model (ELM) message processing route, on the information adoption behavior of young travelers visiting the Millennium Glow Garden tourist attraction, a popular destination among youth due to its high-tech offerings. The study uses data from 385 respondents who have visited this destination with the help of Google Reviews. Multiple linear regression analysis was conducted on the six central route dimensions: information timeliness, information understandability, information relevance, information accuracy, value-added information, and information completeness. The findings provide strong evidence that timely, easily understandable, relevant, accurate, value-added, and complete information significantly influences the information adoption behavior of young travelers. These findings confirm the applicability of central route processing in the ELM within the context of tourism, particularly among young travelers who are closely tied to the digital evolution.